Knockdown of NOVA1 inhibits inflammation and migration of asthmatic airway smooth muscle cells to regulate PTEN/Akt pathway by targeting PTBP1. (October 2021) - Cheng, Ying; Wang, Ning; Zhao, Long; Liu, Cuicui; Wang, Jing; Ma, Cailing; Shi, Xiaolan
Highlights: The expression of NOVA1 induced by TGF-β1 in ASMCs. si-NOVA1 alleviated the TGF-β1-induced inflammation in ASMCs. si-NOVA1 suppressed migration in TGF-β1-induced ASMCs. There was a positive correlation between NOVA1 and PTBP1, si-NOVA1 inhibited PTBP1/PTEN/Akt axis. PTBP1/PTEN/Akt signaling pathway involved in the regulation of NOVA1 on ASMCs. Abstract: NOVA1 (neuro-oncological ventral antigen 1) is a neuron specific RNA binding protein, belonging to the Nova family, which plays an important role in various diseases. However, the role of NOVA1 in childhood asthma remains unclear. This study was aimed to investigate the role of NOVA1 in TGF-β1-induced ASMCs proliferation and migration as well as the potential mechanisms. In our study, the NOVA1 expression was significantly increased in asthmatic tissues and TGF-β1-induced ASMCs. Inhibition of NOVA1 significantly inhibited TGF-β1-induced ASMCs cell proliferation and migration, and alleviates TGF-β1-induced inflammation. NOVA1 positively regulated the PTBP1 expression and si-NOVA1 inhibited the activation of PTEN/AKT signal pathway. Importantly, the overexpression of PTBP1 partially reversed the effect of NOVA1 on cell viability, migration, inflammation and the activation of PTEN/AKT signal pathway. Generally, our study demonstrated that si-NOVA1 inhibited TGF-β1-induced inflammation and migration in ASMCs through PTBP1/PTEN/AKT pathway. Therefore, inhibition of NOVA1 may be useful for the prevention or treatment of asthma airway remodeling.